Ternary metal oxide of CuNiCo2O4nanorods (1D) distributed on g-C3N4 (2D) nanocomposite for non-enzymatic glucose sensing application - R. Thenmozhi; R. Navamathavan (Sensing and Bio-Sensing Research)
Non-enzymatic glucose sensing has a major demand in research community for developing a good glucose sensor. Because enzyme based glucose sensor has several disadvantages such as high cost, difficult fabrication process and instability. To overcome these disadvantages, transition metal oxides (TMO) with g-C3N4 nanocomposite are a good choice for non-enzymatic medium for developing a good glucose sensor. Transition metal oxide has multiple oxidation state, different morphology, high conductivity, enhanced catalytic activity and 2D graphitic carbon nitride has a higher stability. In this work, our particular interest in ternary metal oxide (CuNiCo2O4) nanorods (1D) distributed on surface of the g-C3N4 (2D) nanocomposite were prepared by simple hydrothermal method. The prepared nanocomposite was performed a basic studies such as XRD, FESEM, HRTEM, FTIR, XPS and an electrochemical studies using nickel foam as a current collector. Chronoampermetry analysis produced a sensitivity of 4368 μA Cm−2 mM−1 and low detection limit (LOD) 1.91 μM. The produced response time is 4 s. The measured results of the CuNiCo2O4nanorods (1D) on the surface of g-C3N4 (2D) nanocomposite could be a satisfied material for non-enzymatic glucose sensor.